(untitled) (Annals of Medical Research, 2024)
Aim: Iron deficiency anemia (IDA) is a prevalent nutritional deficiency anemia affecting global populations, characterized by impaired hemoglobin synthesis and erythrocyte dysfunction. Hemoglobin A1c (HbA1c) levels, crucial for monitoring glycemic control in Diabetes Mellitus (DM), may be influenced by factors beyond blood glucose, including anemia. This study aims to evaluate the impact of IDA on HbA1c levels in non-diabetic individuals aged 15-60. Materials and Methods: A retrospective cross-sectional study conducted. The study included 299 IDA patients with FBG and HbA1c levels within the reference range (70-100 mg/dL for FBG, 4%-6.0% for HbA1c) and 114 healthy controls. Exclusion criteria encompassed DM history, recent iron therapy, other anemias, chronic infections, and malnutrition. Patients were grouped by anemia severity regarding hemoglobin levels: mild (11-11.9 g/dL), moderate (10.1-10.9 g/dL), and severe (<10 g/dL). Statistical analysis involved ANOVA, Tukey test, chi-square test, and Pearson correlation, with significance set at p<0.05. Results: Mean HbA1c levels were 5.42±0.34%, 5.48±0.27%, 5.42±0.33%, and 5.28±0.27% in mild, moderate, severe IDA, and control groups, respectively, showing no significant difference among IDA groups but significantly lower in controls (p<0.001). A low negative correlation existed between HbA1c and hemoglobin, iron, and ferritin levels (p<0.01 for Hb and Fe, p<0.05 for ferritin). Age correlated moderately positively with HbA1c (p<0.01). Conclusion: The mechanism of the relationship between iron deficiency anemia and HbA1c levels has not been fully explained. This study highlights the significant influence of IDA on HbA1c levels in non-diabetic individuals aged 15-60, emphasizing the need for larger, prospective studies to clarify this relationship and enhance the interpretation of HbA1c.